Placebo-Controlled Clinical Trial of IncobotulinumtoxinA for Sialorrhea in Children: SIPEXI. (5th October 2021) - Berweck, Steffen; Bonikowski, Marcin; Kim, Heakyung; Althaus, Michael; Flatau-Baqué, Birgit; Mueller, Daniela; Banach, Marta Dagmara
Abstract : Background and Objectives: To investigate the efficacy and safety of repeated injections of incobotulinumtoxinA (incoBoNT/A) for treatment of chronic sialorrhea (drooling) associated with neurologic disorders (e.g., cerebral palsy, traumatic brain injury) or intellectual disability in children and adolescents in a prospective phase III study (SIPEXI [Sialorrhea Pediatric Xeomin Investigation]). Methods: The study enrolled 2- to 17-year-old patients with sialorrhea due to neurologic disorders or intellectual disability. Patients received body weight–dependent doses of incoBoNT/A (20–75 U). A main period with 1 injection cycle (placebo-controlled, double-blind, 6- to 17-year-olds) was followed by an open-label extension with up to 3 further cycles. An additional cohort of 2- to 5-year-olds received active treatment throughout the study. Coprimary endpoints were the change in unstimulated salivary flow rate (uSFR) from baseline to week 4 and the carers' Global Impression of Change Scale (GICS) rating at week 4. Adverse events were recorded. Results: In the main period, 220 patients aged 6–17 years were randomized and treated (148 patients in incoBoNT/A group, 72 patients in placebo group). A total of 35 patients aged 2–5 years received incoBoNT/A (no placebo). A total of 214 patients aged 6–17 years and 33 patients aged 2–5 years continued treatment in the open-label extension period. For the 6- to 17-year-olds, a significant difference between incoBoNT/A and placebo was seen in mean uSFR decrease (difference −0.06 g/min; p = 0.0012) and the carers' GICS rating (difference 0.28 points; p = 0.032) at week 4, in favor of active treatment. The secondary endpoints consistently supported these results. A sustained benefit was observed during the extension. Incidences of adverse events were comparable between incoBoNT/A and placebo and did not increase notably with repeated injections. The most common adverse events were respiratory infections. Efficacy and safety were also favorable in the uncontrolled cohort of 2- to 5-year-olds. Discussion: Both co–primary efficacy endpoints were reached and superiority of incoBoNT/A over placebo was confirmed. IncoBoNT/A (up to 75 U, up to 4 cycles) is an effective and well-tolerated treatment for sialorrhea associated with neurologic disorders in children. Trial Registration Information: Clinicaltrials.gov: NCT02270736 (clinicaltrials.gov/ct2/show/results/NCT02270736 ); EU Clinical Trials Register: 2013-004532-30 (clinicaltrialsregister.eu/ctr-search/search?query=2013-004532-30). Classification of Evidence: This study provides Class I evidence that injection of incobotulinumtoxinA decreases drooling in children aged 6 to 17 years with neurologic disorders.